Protective Factors Against Post Traumatic Stress Disorder (PTSD) Among Disaster Survivors - Razali, Zul Azlin; Md Zin, Ahmad Rostam bin; Omar, Mohd Rahman Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
Post traumatic stress disorder (PTSD) is one of the established complications of any type of disaster. When the victims of a disaster develop PTSD, the complications to their wellbeing can be lifelong and can cross generations. Treatment of PTSD involves multiple approaches and is tedious. However, not everyone that went through disaster will develop this psychiatric disorder. There are personal and societal factors that can protect or reduce the risk of developing PTSD. These protective factors can be classified as social, psychological and spiritual. Identifying the protective factors may be one of the critical elements in the prevention and understanding of this mental illness. It may also help in developing interventions that can be tallied to the community involved. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S18